Ať žijí duchové! hudební komedie plná duchů a podnikavých holek a kluků - Lipský, Oldřich 1924-1986; Lipský, Oldřich 1924-1986; Svěrák, Zdeněk 1936-; Melíšek, Jiří; Vávrová, Dana 1967-2009; Procházka, Jiří 1925-1993; Sovák, Jiří 1920-2000; Uhlíř, Jaroslav (Centrum českého vida, 1996)
"While cavorting around in the ruins of a castle in Prague, a trespassing gang of boys encounter a ghost from the days of knighthood. Naturally enough, they are scared by him. However, when the ghost is caught in a trap set by some other interlopers, they rescue him, and they become allies in a fight to prevent the glorious ruins from being turned into a mushroom farm by the city authorities. Thanks to the involvement of the knight, forest elves are brought in to help their cause."--Clarke Fountain, All Movie Guide
Original: Tschechoslowakei, 1977
Keywords: Ruined buildings / Czech Republic / Prague / Drama; Ghosts plays; Boys / Drama; Elves / Drama; Buildings / Repair and reconstruction / Drama; Motion pictures / Czech Republic; Boys; Buildings / Repair and reconstruction; Elves; Motion pictures; Ruined buildings; Czech Republic; Czech Republic / Prague; Children's films; Comedy films; Drama; Feature films; Juvenile works; Musical films; Films pour enfants; Films musicaux; Films comiques